Governing complexity and environmental justice: lessons from the water crisis in Metropolitan São Paulo (2013-2015) - Torres, Pedro Henrique Campello; Côrtes, Pedro Luiz; Jacobi, Pedro Roberto (Desenvolvimento e Meio Ambiente, 2020)
The paper presents a discussion on the water crisis that occurred between 2013 and 2015 in the Metropolitan Region of São Paulo, the lack of integrated natural resources planning, and the reaction of social actors affected by the crisis. The region was affected by an extreme hydrological and climatological event, which was combined with the unsustainable management of water resources. The paper addresses, initially, the dynamics of water governance in the region, and the main aspects related to water availability and climate dependence that caused the water crisis. Then, we present an analysis of the process that led to the water crisis and its main developments, which is based on the follow-up of the different moments of the crisis and dialogues with its relevant stakeholders. The results indicate the relevance of emphasizing issues on matters such as the lack of transparency and highlight the role of societal initiatives. We conclude the paper with a proposition to discuss governance processes that can contribute to the development of more effective initiatives in order to reduce the impact of this visible change in water regimes, strengthen transparent management, and promote a more democratic interaction between social actors and the government.